Chiral 2d theories from N = 4 SYM with varying coupling - Lawrie, Craig; Schäfer-Nameki, Sakura; Weigand, Timo (Journal of high energy physics, 2017)
We study 2d chiral theories arising from 4d N = 4 Super-Yang Mills (SYM) with varying coupling τ . The 2d theory is obtained by dimensional reduction of N = 4 SYM on a complex curve with a partial topological twist that accounts for the non-constant τ. The resulting 2d theories can preserve (0,n) with n = 2,4,6,8 chiral supersymmetry, and have a natural realization in terms of strings from wrapped D3-branes in F-theory. We determine the twisted dimensional reduction, as well as the spectrum and anomaly polynomials of the resulting strings in various dimensions. We complement this by considering the dual M-theory configurations, which can either be realized in terms of M5-branes wrapped on complex surfaces, or M2-branes on curves that result in 1d supersymmetric quantum mechanics.